Effect of air pollution on element profile and radioactive compounds in six tree species - Turfan, Nezahat; Kurnaz, Aslı; Sarıyıldız, Temel (Bursa Teknik Üniversitesi, 2021)
Variation in macro and micronutrients and radioactivities (238U, 232Th, 137Cs, and 40K) due to air pollution was studied using six tree species: maple (Acer negundo), cypress (Cupressus arizonica) ash-tree (Fraxinus excelsior), pine (Pinus nigra), plane tree (Platanus orientalis), and poplar (Populus nigra). Tree leaf samples were collected in 2016 and 2017 from a rural area (control site) and urban area (polluted site) with high population, heavy traffic, and small industrial activity. The results showed that for the 2016 and 2017, mean Mg, S and K concentration was higher at the polluted sites than at the control sites for the most tree species, except ash-tree for Mg, ash-tree and plane tree for S and maple tree for K respectively. Mean P concentration was lower at the polluted sites for maple, pine, plane tree and poplar trees, while it was higher for cypress and ash trees. Mean Ca concentration at the polluted sites was lower for maple, cypress, pine and plane tree leaves, but higher for ash tree and populous tree species. Most micronutrients were generally higher at the polluted sites compared to the control sites for all tree species. Only, Co concentration was lower for ash tree and pine tree species, and Mn concentration was lower for poplar tree at the polluted site compared to the control site. The activity concentration of trees was recorded as 40K > 232Th > 238U >137Cs in 2016, while they were noted as 40K>238U>232Th>137Cs in 2017. The plane tree had the lowest activity concentration for both years. Taking all data into an account, the order of trees at the polluted sites was determined as poplar > ash tree > maple > pine > plane tree = cypress for 2016, while this order was recorded as poplar > cypress = maple > ash tree > pine = plane tree for 2017. It can be concluded that poplar, ash tree, and maple could be recommended for future biomonitoring research in order to improve air quality in urban areas.
Keywords: Forest Industry Engineering; Orman Endüstri Mühendisliği